Careers guidance: an international perspective - Watts, Anthony G. (1999)
The rationales for comparative studies of guidance systems are outlined. The key differences between guidance systems in different countries can be related to stage of economic development, to the political system, to social and cultural factors, to the education and training system, and to professional and organisational structures. The competing pressures towards convergence and divergence between guidance systems are explored.